Insulating coating powder
Through the combination of epoxy resin, phenolic resin and inorganic filler, the insulation performance and color maintenance problems of the anhydride system materials in high humidity and high temperature are solved, and efficient insulation coating powder is provided for new energy vehicle motors, avoiding acid anhydride The environmental and health effects of the material and the color adjustment is achieved.
Patent Information
- Application Number
- CN202411394597.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
The existing insulating coating materials of the acid anhydride system are insufficient in humidity and heat resistance in high humidity environments, and the release of volatile organic compounds during curing is not good for the environment and human health. At the same time, it is difficult to maintain the original color under high temperature conditions, which affects its electronics. Practicality in the automotive field.
An insulating coating powder combining epoxy resin, phenolic resin, inorganic filler and colorant is used to form a coating material with excellent insulating properties and yellowing resistance through a specific proportion of mixing and heating and pressurization.
Effectively improve the insulation performance, avoid the release of volatile organic compounds of the acid anhydride material, and adjust the color through colorant, solve the color maintenance problem of the material under high temperature conditions, and meet the application of stator flat copper wire for new energy vehicle motors Application standards.
Smart Images

Figure BDA0005073406090000071 
Figure BDA0005073406090000081 
Figure BDA0005073406090000091
Abstract
Description
Technical field:
[0001] The invention relates to the fields of polymer materials and electronic automobiles, and in particular to an insulating coating powder. Technical background:
[0002] In recent years, the new energy vehicle industry has developed rapidly. In addition to policy and environmental factors, the continuous updating and iteration of technology is the main driving force for the development of the industry. As the core component of new energy vehicles, the drive motor provides the power source for the whole vehicle and naturally attracts widespread attention. The demand for drive motors of the whole vehicle can be summarized into the following four aspects, namely high efficiency, high power density, low cost and low noise and vibration (NVH). Flat copper wire winding technology meets the above-mentioned demand for drive motors of the whole vehicle due to its superior performance in slot fill rate, thermal conductivity, armature rigidity and automated production. Therefore, it has been widely recognized by the new energy industry once it was launched and has become the mainstream development direction of drive motor technology.
[0003] The traditional insulating coating materials used for the surface of flat copper wire are mostly acid anhydride system materials, and the use of such materials has at least the following problems:
[0004] 1. The epoxy resin of the existing acid anhydride system material has deficiencies in moisture and heat resistance, which may affect its insulation performance as an insulating coating material in a high humidity environment. At the same time, the acid anhydride curing agent releases volatile organic compounds during the curing process, which has an adverse effect on the environment and human health.
[0005] 2. Existing acid anhydride system materials have problems in yellowing resistance as insulating coating materials. It is difficult for the materials to maintain their original color when exposed to light or high temperature for a long time, which affects their practicality in the field of electronic automobiles.
[0006] The prior art has the above problems and is difficult to solve, and cannot meet the requirements of being used as a coating powder for flat copper wire. Therefore, we propose an insulating coating powder. Summary of the invention:
[0007] The embodiment of the application solves the problem that the prior art cannot be used as a good coating material for flat copper wires by providing an insulating coating powder, thereby achieving the technical effect of being able to be used as a good coating material for flat copper wires.
[0008] In a first aspect, an embodiment of the present application provides an insulating coating powder, the composition components of which include: an insulating coating powder, the composition raw materials of which include: epoxy resin, phenolic resin, inorganic filler and colorant.
[0009] Furthermore, the epoxy resin can be a mixture of biphenyl type, multifunctional type, o-cresol type, and dicyclopentadiene type, and the phenolic resin can be a mixture of bisphenol A type, phenol formaldehyde type, o-cresol formaldehyde type, aralkylphenol type, biphenyl type, hydroxybenzaldehyde type, and polybenzonitrile phenol formaldehyde type.
[0010] Furthermore, the inorganic filler is two or three of molten spherical, molten angular and crystalline silica, accounting for 35% to 60% by mass in the composition; the colorant is one of carbon black, yellow iron oxide and benzidine orange, accounting for 0% to 2% by mass in the composition.
[0011] Preferably, the colorant is yellow iron oxide, and titanium oxide needs to be added to the inorganic filler to make the color of the cured material purer.
[0012] Preferably, the fused silica is spherical silicon powder with a cut-off point of less than 75 μm and an average particle size of 18 to 27 μm.
[0013] Furthermore, the composition further comprises any one or more of a curing accelerator, a release agent, a coupling agent and a flame retardant.
[0014] Furthermore, the curing accelerator is at least one of an organic phosphorus compound, an adduct of an organic phosphorus compound and a quinone compound, a tertiary amine type DBU series, and an imidazole compound; the release agent is montan wax, fatty acid ester, silicone oil, or a combination thereof; the coupling agent is one or more of trimethoxysilane, mercaptopropyl trimethoxysilane, phenylaminopropyl trimethoxysilane, and γ-glycidyloxypropyl trimethoxysilane; and the flame retardant is a metal hydroxide, an oxide of an organic phosphorus compound, or a combination thereof.
[0015] Furthermore, the epoxy resin added in the composition is 15% to 40% by mass, and the phenolic resin added is 10% to 30% by mass.
[0016] Furthermore, calculated by mass percentage, the composition includes 15% to 40% epoxy resin, 10% to 30% phenolic resin, 35% to 60% inorganic filler, 0.1% to 3% curing accelerator, and 0.1% to 10% of the total weight of release agent, flame retardant, coupling agent, colorant and other materials.
[0017] The materials are used in combination in the above proportions and should have the following properties after curing to meet the requirements of flat copper wire coating materials:
[0018] The color is one of black, white, golden yellow, and orange;
[0019] Gel time (200°C) is 20 to 30 seconds (SJ-T11197-2013)
[0020] Glass transition temperature is 150℃~180℃(SJ-T11197-2013);
[0021] Thermal expansion coefficient (α1) is 30ppm~70ppm (SJ-T11197-2013);
[0022] Thermal expansion coefficient (α2) is 100ppm~130ppm (SJ-T11197-2013);
[0023] Bending strength: 50MPa~130MPa (GBT 1449-2005)
[0024] In a second aspect, the present invention further provides a method for preparing an insulating coating powder, comprising the following steps:
[0025] S1: weighing the raw materials according to the components and weight percentages, and uniformly mixing the required added materials in a high-speed stirring mixer according to the proportions, with a stirring speed of 800 to 2000 r / min to obtain a premix;
[0026] S2: Extruding and crushing the premix at a certain temperature to obtain an epoxy resin composition
[0027] S3: The premix is heated and pressurized at a certain temperature, mixed, extruded and crushed to obtain the product.
[0028] In the third aspect, the present invention also provides an application of an insulating coating powder, and the material is used for coating the stator flat copper wire of a new energy vehicle motor, wherein the flat copper wire is made of a copper material wrapped by an enameled wire, and the enameled wire is one of polyimide, polyesterimide, polyamideimide, etc., and the copper material can be one of pure copper (3N), oxygen-free copper, annealed copper, copper (such as copper-silver, copper-tin, etc.) alloy, etc.
[0029] The present invention adopts an insulating coating material obtained by combining epoxy resin, phenolic resin, curing accelerator, inorganic filler, colorant and other additives, wherein the inorganic filler is molten spherical, molten angular and crystalline silicon dioxide with a mass proportion of 35% to 60%, which can meet the application standards as flat copper wire coating powder, and effectively avoids the existing insulating materials under the acid anhydride material system that may affect its insulating performance as an insulating coating material in a high temperature environment. At the same time, the acid anhydride curing agent releases volatile organic compounds during the curing process, which has an adverse effect on the environment and human health.
[0030] The present invention uses carbon black, yellow iron oxide, and benzidine orange as colorants with a mass ratio of 0% to 2%, which effectively avoids the problem of yellowing resistance of existing acid anhydride system materials as insulating coating materials. It is difficult for materials to maintain their original color when exposed to light or high temperature for a long time, which affects their practicality in the field of electronic vehicles. The epoxy curing material system can present the desired color such as white, orange, and gold, rather than being limited to the traditional black plastic package.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The insulating coating powder of the present invention replaces the existing acid anhydride system material and is applied to the stator flat copper wire coating of the new energy vehicle motor, thereby avoiding the adverse effects of the volatilization of the acid anhydride material on the human body. The insulating performance of the insulating coating material under high temperature conditions is effectively improved by adding components such as inorganic fillers with a specific mass ratio. After testing, the gelation time, glass transition temperature, thermal expansion coefficient, thermal expansion coefficient, and bending strength of the insulating coating powder meet the application standards of the flat copper wire coating powder.
[0033] Secondly, carbon black, yellow iron oxide and benzidine orange with a mass proportion of 0% to 2% are used as colorants to make the epoxy curing material system present the desired color such as white, orange and gold, which changes the long-standing yellowing resistance problem of acid anhydride system materials; and the preparation process of the insulating coating powder of the present invention is relatively simple and has high reliability, and has broad application prospects in the field of stator flat copper wire coating of new energy vehicle motors. Specific embodiment:
[0034] In terms of catalyst selection, organic phosphorus compounds, adducts of organic phosphorus compounds and quinone compounds, and imidazole compounds have the opportunity to achieve resins with the same properties by combining them in proportion, only from the perspective of gelation time, viscosity, flexural strength and other tests. However, considering the cost application (for example, the price of adducts of organic phosphorus compounds and quinone compounds was ten times that of organic phosphorus compounds in the year when this article was written, while imidazole compounds have better delay and their cost is slightly lower than that of adducts of organic phosphorus compounds and quinone compounds), the combination or single use of imidazole compounds can be more competitive in this type of application at the time point when this article was written.
[0035] In the use of flame retardants, ammonia catalysts have a certain catalytic effect on the resin system. In this type of application, they can deal with the ultra-long fluidity caused by the low filler content and have a certain positive optimization effect; metal hydroxide catalysts have better flame retardant advantages when the volume of the plastic body is large after plastic sealing and curing because of their flame retardant principle that the generated water vapor absorbs heat; organic phosphorus compounds have better flame retardant advantages when the volume of the plastic body is small after plastic sealing and curing, especially when the thickness is thin, because there are more residual carbon elements in aromatic hydrocarbons, it is easier to form dense carbides to isolate oxygen and provide flame retardant principles. Because the application volume of motor rotors spans a large range, comprehensive addition can provide more comprehensive flame retardant capabilities.
[0036] In the use of release agents, stearic acid ester wax has a higher polarity, and its alcohol group end group usually has better bonding and dispersion ability with the resin system, and its saturated alkyl end group has a higher affinity with the monovalent or polyvalent alcohol end group of ester wax with lower polarity; ester wax has a lower polarity and is easy to float to the surface of the plastic package to provide demolding ability, but its dispersion ability is insufficient in the resin environment (when both are in a high-temperature molten state), and there is a phenomenon of clumping and aggregation. The combination of the two can simultaneously give the composition the characteristics of demolding force and uniformity of demolding position.
[0037] Example 1
[0038] An insulating coating powder provided by an embodiment of the present invention has a specific composition formula as shown in Table 1;
[0039] Table 1: A formulation of insulating coating powder
[0040]
[0041] According to the composition formula in Table 1, the steps for preparing an insulating coating powder provided by an embodiment of the present invention are as follows:
[0042] The raw materials are uniformly mixed in a high-speed stirring mixer to form a premix;
[0043] The premix is extruded and crushed at a certain temperature to obtain a preliminary composition;
[0044] Then, the preliminary composition is subjected to heating and pressure treatment at a set temperature and pressure to promote chemical reaction and physical bonding between components;
[0045] Finally, the heated and pressurized mixture is mixed and extruded again through an extruder, and crushed to a desired particle size to obtain the final product.
[0046] Example 2
[0047] An insulating coating powder provided in an embodiment of the present invention has a specific composition formula as shown in Table 2;
[0048] Table 2: Composition of an insulating coating powder formula
[0049]
[0050] According to the composition formula in Table 2, the steps for preparing an insulating coating powder provided by an embodiment of the present invention are as follows:
[0051] The raw materials are uniformly mixed in a high-speed stirring mixer to form a premix;
[0052] The premix is extruded and crushed at a certain temperature to obtain a preliminary composition;
[0053] Then, the preliminary composition is subjected to heating and pressure treatment at a set temperature and pressure to promote chemical reaction and physical bonding between components;
[0054] Finally, the heated and pressurized mixture is mixed and extruded again through an extruder, and crushed to a desired particle size to obtain the final product.
[0055] Example 3
[0056] An insulating coating powder provided in an embodiment of the present invention has a specific composition formula as shown in Table 3;
[0057] Table 3: Composition of an insulating coating powder formula
[0058]
[0059] According to the composition formula in Table 3, the steps for preparing an insulating coating powder provided by an embodiment of the present invention are as follows:
[0060] The raw materials are uniformly mixed in a high-speed stirring mixer to form a premix;
[0061] The premix is extruded and crushed at a certain temperature to obtain a preliminary composition;
[0062] Then, the preliminary composition is subjected to heating and pressure treatment at a set temperature and pressure to promote chemical reaction and physical bonding between components;
[0063] Finally, the heated and pressurized mixture is mixed and extruded again through an extruder, and crushed to a desired particle size to obtain the final product.
[0064] Example 4
[0065] An insulating coating powder provided in an embodiment of the present invention has a specific composition formula as shown in Table 4;
[0066] Table 4: Composition of an insulating coating powder formula
[0067]
[0068]
[0069] According to the composition formula in Table 4, the steps for preparing an insulating coating powder provided by an embodiment of the present invention are as follows:
[0070] The raw materials are uniformly mixed in a high-speed stirring mixer to form a premix;
[0071] The premix is extruded and crushed at a certain temperature to obtain a preliminary composition;
[0072] Then, the preliminary composition is subjected to heating and pressure treatment at a set temperature and pressure to promote chemical reaction and physical bonding between components;
[0073] Finally, the heated and pressurized mixture is mixed and extruded again through an extruder, and crushed to a desired particle size to obtain the final product.
[0074] Example 5
[0075] An insulating coating powder provided in an embodiment of the present invention has a specific composition formula as shown in Table 5;
[0076] Table 5: Composition of an insulating coating powder formula
[0077]
[0078]
[0079] According to the composition formula in Table 5, the steps for preparing an insulating coating powder provided by an embodiment of the present invention are as follows:
[0080] The raw materials are uniformly mixed in a high-speed stirring mixer to form a premix;
[0081] The premix is extruded and crushed at a certain temperature to obtain a preliminary composition;
[0082] Then, the preliminary composition is subjected to heating and pressure treatment at a set temperature and pressure to promote chemical reaction and physical bonding between components;
[0083] Finally, the heated and pressurized mixture is mixed and extruded again through an extruder, and crushed to a desired particle size to obtain the final product.
[0084] Example 6
[0085] An insulating coating powder provided in an embodiment of the present invention has a specific composition formula as shown in Table 6;
[0086] Table 6: Composition of an insulating coating powder formula
[0087]
[0088] According to the composition formula in Table 6, the steps for preparing an insulating coating powder provided by an embodiment of the present invention are as follows:
[0089] The raw materials are uniformly mixed in a high-speed stirring mixer to form a premix;
[0090] The premix is extruded and crushed at a certain temperature to obtain a preliminary composition;
[0091] Then, the preliminary composition is subjected to heating and pressure treatment at a set temperature and pressure to promote chemical reaction and physical bonding between components;
[0092] Finally, the heated and pressurized mixture is mixed and extruded again through an extruder, and crushed to a desired particle size to obtain the final product.
[0093] Test Example 1: Performance test of the insulating coating powder prepared in Examples 1 to 6
[0094] Part I: Experimental Methods
[0095] The performance test of the insulating coating powder prepared in Examples 1 to 6 of the present invention was carried out, and the specific test method is as follows:
[0096] 1. Gel time: According to the method described in Article 5.3 Gel time of SJ / T 11197-1999 Epoxy Molding Plastics, the gel time (s) is measured. The epoxy molding plastic is placed on a curing plate heated to 175°C, and the time is measured with a stopwatch. The sample is stirred evenly with the front end of a scraper. When the sample gels, the stopwatch is stopped and the time recorded is the gel time.
[0097] Result determination: After the gelation time test, if the gelation time is less than 20s or greater than 30s, which is insufficient to meet the coating process requirements, the result is determined to be poor; if the gelation time is greater than 20s and less than 30s, which meets the coating process requirements, the result is determined to be good.
[0098] 2. Glass transition temperature (Tg): Set certain experimental conditions according to the DSC method specified in Section 2.4.25 of IPC-TM-650 standard, then place the sample in the DSC analyzer and heat it according to the standard procedure. Observe the DSC curve, identify the turning point of the thermal event of the sample during the heating process, and determine the midpoint of the baseline on the curve. This point is the glass transition temperature (Tg) of the material.
[0099] 3. Thermal expansion coefficient: Select a suitable thermomechanical analyzer (TMA) and set the equipment parameters according to the standard test method. Place the sample on the TMA equipment and heat it according to the specified test conditions. By analyzing the TMA curve, determine the length change rate of the sample in a specific temperature range. Use this change rate and the corresponding temperature change to calculate the values of the thermal expansion coefficients α1 and α2.
[0100] 4. Bending strength: Set the test parameters on the universal material testing machine according to GB / T 2567-2021, including span and loading speed, to ensure standardized test conditions; record the stress-strain data of the sample during the force process until the sample is damaged; analyze the obtained stress-strain curve and read the maximum stress value from the curve, which represents the bending strength of the sample.
[0101] 5. Viscosity test: Low viscosity materials can give the materials higher solubility during the extrusion liquefaction process.
[0102] Part II: Test Results
[0103] According to the detection method of the first part, the performance test of the insulating coating powder prepared in Examples 1 to 6 of the present invention was carried out, and the specific test results are shown in Table 7;
[0104] Table 7: Performance test results of the insulating coating powder prepared in Examples 1 to 6
[0105]
[0106] From the results in Table 7, it can be seen that the color of the insulating coating powder prepared in Examples 1-6 can be produced by adding colorants to produce corresponding colors. At the same time, the addition or cancellation of special pigments has no adverse effect on the key characteristics of the material in the application of the rotor core. In the actual production and application process, the production cleaning level is sufficient to meet the shipping conditions. The gelation time at 200 degrees Celsius is between 20 and 35 seconds, the glass transition temperature at 175 degrees Celsius is between 150°C and 170°C, the thermal expansion coefficient α1 is between 30 and 70ppm, the thermal expansion coefficient α2 is between 100 and 130ppm, and the bending strength is between 50 and 110MPa. Among them, the coating powder prepared in Example 1 and Examples 4-6 has better effect. It can be seen that the composite epoxy resin component, content, and curing accelerator component and content in the coating powder have a greater influence on the performance of the coating powder. It has better compatibility within the specific component formula and content range, and the prepared coating powder has better performance.
[0107] Comparative Example 1
[0108] The difference between this comparative example and Example 1 is that: o-cresol type epoxy resin 2 (epoxy resin 2) and fatty acid ester wax (release agent 1) are not added, the organic phosphorus compound (curing accelerator 1) is replaced by an adduct of an organic phosphorus compound and a quinone compound (curing accelerator 2), an inorganic filler is used to make up the mass, the amount of inorganic filler added is 67.01%, and the other ingredients and preparation method are consistent with Example 1.
[0109] Comparative Example 2
[0110] The difference between this comparative example and Example 1 is that the added ingredients are the same, except that the contents of the other ingredients except the inorganic filler are reduced, the added amount of the inorganic filler is 57.21%, and the other ingredients and preparation method are consistent with Example 1.
[0111] Test Example 1: Performance test of the insulating coating powder prepared in Comparative Examples 1 to 2
[0112] In this test example, the performance of the insulating coating powder prepared in Comparative Examples 1 to 2 was tested. The test method was consistent with that of Test Example 1. The test results are shown in Table 8.
[0113] Table 8: Performance test results of the insulating coating powder prepared in Comparative Examples 1 to 2
[0114]
[0115] Comparing the results of Table 7 and Table 8, it can be seen that when the amount of inorganic filler added is too high (greater than 60%), the gelation time is less than 20s, which is not enough to meet the coating process requirements. When the inorganic filler is controlled in the range of 40% to 60%, the gelation time is greater than 20s, which can meet the coating process requirements. Compared with the comparative example, the viscosity of Examples 1-6 is less than that of the comparative example, and it can have higher compatibility during the extrusion liquefaction process. By adjusting the type and amount of pigment added, the epoxy curing material system can present the desired color such as white, orange, and gold, rather than being limited to the usual black plastic seal.
[0116] Comparative Example 3
[0117] No. 1: The difference between this comparative example and Example 1 is that the mass proportion of the inorganic filler fused spherical silica is less than 40%, and the mass is made up by o-cresol type epoxy resin 1 and o-cresol type epoxy resin 2, and the other ingredients and preparation method are consistent with Example 1.
[0118] No. 2: The difference between this comparative example and Example 1 is that the mass proportion of the inorganic filler fused spherical silica is greater than 60%, and the other ingredients and preparation method are consistent with those of Example 1.
[0119] Test Example 2: Performance test of the insulating coating powder prepared in Comparative Example 3
[0120] In this test example, the performance of the insulating coating powder prepared in comparative example 3 was tested. The test method was consistent with that of test example 1. The test results are shown in Table 9.
[0121] Table 9: Performance test results of the insulating coating powder prepared in Comparative Example 3
[0122]
[0123] From the results in Table 9, it can be seen that the performance of the two groups of insulating coating powders prepared in Comparative Example 3 is significantly lower than that of the insulating coating powder prepared in Example 1. It can be seen that the mixing ratio of the inorganic filler in the insulating coating powder of the present invention has a great influence on the performance of the coating powder. When the mass proportion of the inorganic filler is 40% to 60%, the prepared coating powder has excellent performance.
[0124] Comparative Example 4
[0125] No. 3: The difference between this comparative example and Example 5 is that titanium oxide is not added, and molten spherical silica is used to make up the mass. The other ingredients and preparation method are consistent with Example 5.
[0126] No. 4: The ingredients and proportions of this comparative example are slightly different from those of Example 5, and the preparation method is consistent with that of Example 5.
[0127] Test Example 3: Performance test of the insulating coating powder prepared in Comparative Example 4
[0128] In this test example, the performance of the insulating coating powder prepared in comparative example 4 was tested. The test method was consistent with that of test example 1. The test results are shown in Table 10.
[0129]
[0130] It can be seen from the results in Table 10 that in the coating powder of No. 3 in Comparative Example 4, only iron oxide yellow (colorant 2) was added when adding the colorant, and the color of the obtained coating powder was far from the expected gold color, was not obvious, and the purity was insufficient. However, No. 4 added titanium oxide while adding iron oxide yellow, and the color of the prepared coating powder was gold, which was the expected color.
[0131] Comparative Example 5
[0132] No. 5: The difference between this comparative example and Example 1 is that the mass proportion of the added o-cresol type epoxy resin 2 in this comparative example is significantly smaller than that in Example 1, and molten spherical silica is used to make up the mass. The other ingredients and preparation method are consistent with those in Example 1.
[0133] No. 6: The difference between this comparative example and Example 1 is that the mass proportion of the o-cresol type epoxy resin 2 added in this comparative example is slightly different from that in Example 1, and molten spherical silica is used to make up the mass. The other ingredients and preparation method are consistent with those in Example 1.
[0134] No. 7: The difference between this comparative example and Example 1 is that the mass proportion of the added o-cresol type epoxy resin 2 in this comparative example is greater than that in Example 1, molten spherical silica is used to make up the mass, and the other ingredients and preparation method are consistent with those in Example 1.
[0135] Test Example 3: Performance test of the insulating coating powder prepared in Comparative Example 5
[0136] In this test example, the performance of the insulating coating powder prepared in comparative example 5 was tested. The test method was consistent with that of test example 1. The test results are shown in Table 11.
[0137]
[0138]
[0139] As can be seen from the results in Table 11, the content of the o-cresol epoxy resin 2 of No. 5 in Comparative Example 5 is much less than that of Example 1, the content of the o-cresol epoxy resin 2 of No. 6 is similar to that of Example 1, and the content of the o-cresol epoxy resin 2 of No. 7 is much greater than that of Example 1. The o-cresol epoxy resin 2 of No. 5 and No. 7 is too large or too small, which leads to a decrease or increase in gelation time, which is not within the range of the operable process, is not conducive to the normal progress of the process, and its viscosity is not compatible with the expected product. Therefore, the proportion of high-viscosity o-cresol resin 2 is moderate, which can better balance the problem of shortening the gelation time caused by the increase in filler content. Such a combination can provide higher compatibility than single material properties.
[0140] The insulating coating powder of the present invention replaces the existing acid anhydride system material and is applied to the stator flat copper wire coating of the new energy vehicle motor, thereby avoiding the adverse effects of the volatilization of the acid anhydride material on the human body. The insulating performance of the insulating coating powder as an insulating coating material under high temperature conditions is effectively improved by adding components such as inorganic fillers with a specific mass proportion. After testing, its gel time, glass transition temperature, thermal expansion coefficient α1, thermal expansion coefficient α2, viscosity, and bending strength all meet the application standards of the flat copper wire coating powder; secondly, carbon black, iron oxide yellow, and benzidine orange with a mass proportion of 0% to 2% are used as colorants to make the epoxy curing material system present the desired color such as white, orange, and gold, which changes the long-standing yellowing resistance problem of the acid anhydride system material; and the insulating coating powder of the present invention has a relatively simple preparation process and has high reliability, and has broad application prospects in the field of stator flat copper wire coating of new energy vehicle motors. It should be noted that, in order to make the description concise, not all possible combinations of the various technical features in the above embodiments are described. The above embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in the field, without departing from the concept of the present invention, the technicians in the field can combine and combine the different embodiments and features of the different embodiments described in this specification, which all belong to the protection scope of the present invention.
Claims
1. An insulating coating powder, characterized in that: The raw materials of the composition include: epoxy resin, phenolic resin, inorganic filler and colorant, wherein the epoxy resin is a mixture obtained by uniformly mixing biphenyl type, multifunctional type, o-cresol type and dicyclopentadiene type, and the phenolic resin is a mixture obtained by uniformly mixing bisphenol A type, phenol formaldehyde type, o-cresol formaldehyde type, aralkylphenol type, biphenyl type, hydroxybenzaldehyde type and polybenzonitrile phenol formaldehyde type; the inorganic filler is two or three of molten spherical, molten angular and crystalline silica, accounting for 35% to 60% by mass in the composition; the colorant is one of carbon black, iron oxide yellow and benzidine orange, accounting for 0% to 2% by mass in the composition.
2. The insulating coating powder according to claim 1, characterized in that: The composition further comprises any one or more of a curing accelerator, a mold release agent, a coupling agent and a flame retardant.
3. An insulating coating powder according to claim 2, wherein: The curing accelerator is at least one of an organic phosphorus compound, an adduct of an organic phosphorus compound and a quinone compound, a tertiary amine type DBU series, and an imidazole compound; the release agent is montan wax, fatty acid ester, silicone oil, or a combination thereof; the coupling agent is one or more of trimethoxysilane, mercaptopropyl trimethoxysilane, phenylaminopropyl trimethoxysilane, and γ-glycidyloxypropyl trimethoxysilane; and the flame retardant is a metal hydroxide, an oxide of an organic phosphorus compound, or a combination thereof.
4. The insulating coating powder according to claim 1, characterized in that: The fused silica is spherical silicon powder with a cut-off point of less than 75 μm and an average particle size of 18 to 27 μm.
5. The colorant added to the insulating coating powder according to claim 1, characterized in that: When choosing yellow iron oxide as a colorant, it is necessary to combine it with titanium oxide in the inorganic filler to make the color of the material purer after curing.
6. The insulating coating powder according to any one of claims 1 to 5, characterized in that: The epoxy resin added in the composition is 15% to 40% by weight, and the phenolic resin added is 10% to 30% by weight.
7. An insulating coating powder according to claim 6, characterized in that: Calculated by mass percentage, the composition includes 15% to 40% epoxy resin, 10% to 30% phenolic resin, 35% to 60% inorganic filler, 0.1% to 3% curing accelerator, and 0.1% to 10% of the total weight of release agent, flame retardant, coupling agent, colorant and other materials.
8. A method for preparing the insulating coating powder according to claims 1 to 8, characterized in that: The following steps are involved: S1: weighing the raw materials according to the components and weight percentages, and uniformly mixing the required added materials in a high-speed stirring mixer according to the proportions, with a stirring speed of 800 to 2000 r / min to obtain a premix; S2: Extruding and crushing the premix at a certain temperature to obtain an epoxy resin composition S3: The premix is heated and pressurized at a certain temperature, mixed, extruded and crushed to obtain the product.
9. An application of the insulating coating powder prepared according to claims 1-8, wherein: The material is used for coating the stator flat copper wire of the new energy vehicle motor, wherein the flat copper wire is made of copper material wrapped by enameled wire, the enameled wire is one of polyimide, polyesterimide, polyamideimide, etc., and the copper material can be one of pure copper (3N), oxygen-free copper, annealed copper, copper (such as copper-silver, copper-tin, etc.) alloy, etc.
Citation Information
Patent Citations
Epoxy resin composition for semiconductor encapsulation, cured product thereof, and semiconductor device using epoxy resin composition
CN102666724A
High-adhesion epoxy molding compound for packaging semiconductor
CN106674911A
High temperature resistant epoxy powder composition and preparation method thereof
CN109825170A
Copper wire compatible corrosion-resistant epoxy resin composition and preparation method thereof
CN110128782A
Epoxy resin powder coating
JP2006273900A
Cited By
Motor rotor magnetic adhesive for improving high-temperature magnetic flux, and motor rotor
WO2026123595A1
